Perspectivas epistemológicas e pedagógicas da pesquisa em educação e tecnologias digitais: um estudo das dissertações de mestrado do programa de pós-graduação em educação da Universidade Federal de Minas Gerais, no período de 2000 a 2014 - Humberto Rocha de Souza (2018)
This master's dissertation refers to one of the biggest problems involving pedagogical work and teaching training in contemporary form the insertion of digital technologies into the teaching processes is initial or continued. The object of the reflections were 06 master's dissertations elaborated and defended within the graduate program in Education of the Federal University of Minas Gerais (UFMG) between 2000 and 2014. We question and reflect on the epistemological and pedagogical foundations related to the theory of knowledge of dissertations on the training of teachers mediated by digital technologies and what limits and possibilities they present to the Understanding and training of the teaching workers category. The objective was to investigate what the epistemological and pedagogical trends and perspectives that substantiate and guide the research on digital technology and teacher training. The reflections were based on the following questions: a) which methodological approaches were used in the master's dissertations defended and approved within the graduate program in Education of the Faculty of Education of the Federal University of Minas Gerais? B. What are the pedagogical foundations that are supported in these dissertations? C) What are the epistemological tendencies of these surveys and what relationships establish with the pedagogical foundations advocated in these studies? We point out that one of the structuring aspects of the production of knowledge about the training of teachers mediated by digital technologies directed to the working class falls into a dialectic perspective that breaks with the phenomenal world and Fetishized of the phenomenon investigated, centered on the socialization and appropriation of the scientific technical basis, through a school education that provides access to all.